2003
DOI: 10.1002/cncr.11339
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of ovarian cancer in the United States, 1992-1997

Abstract: Ͼ 30 demographic and clinical variables. The unprecedented size of the file, which includes information for Ͼ 653,000 cases submitted from registries meeting national standards of high data quality, provides extensive opportunities for research on cancer incidence patterns that would not otherwise be possible. This supplement represents one area of research produced from this resource. A description of the NAACCR file data elements can be found in the Table 1. No additional data collection or pathology verific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 53 publications
1
24
0
2
Order By: Relevance
“…We found that PFTCs were most often unilateral and diagnosed slightly more often at a localized stage than at regional or distant stages. This is in contrast to ovarian cancer, where over 50% of malignant tumors are diagnosed at a distant stage [30]. The difference between PFTC and ovarian cancer in stage at diagnosis may be primarily due to the fact that signs and symptoms such as abnormal vaginal bleeding or discharge and abdominal pain together with an abdominal mass are largely present for women with PFTC, while this is not the case for many women with ovarian cancer, allowing for an earlier stage at diagnosis for PFTC [27].…”
Section: Discussionmentioning
confidence: 88%
“…We found that PFTCs were most often unilateral and diagnosed slightly more often at a localized stage than at regional or distant stages. This is in contrast to ovarian cancer, where over 50% of malignant tumors are diagnosed at a distant stage [30]. The difference between PFTC and ovarian cancer in stage at diagnosis may be primarily due to the fact that signs and symptoms such as abnormal vaginal bleeding or discharge and abdominal pain together with an abdominal mass are largely present for women with PFTC, while this is not the case for many women with ovarian cancer, allowing for an earlier stage at diagnosis for PFTC [27].…”
Section: Discussionmentioning
confidence: 88%
“…Thus, the role of decreased SELENBP1 in ovarian cancer prognosis is not clear. Ovarian cancer remains the most lethal gynecologic malignancy for women and it represents 2.5% total cancer deaths in the United States [23][24][25][26]. Identifying altered SELENBP1 expression may be significant for the treatment of ovarian cancer since selenium has been shown to have an important role in the reduction and prevention of other cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of symptoms in early-stage disease often means that the disease is diagnosed at a late stage, resulting in poor overall 5-year survival. 1,2 Most ovarian tumours are categorised as either epithelial, germ cell or sex cord tumours. Epithelial tumours, which are thought to arise from the ovarian surface epithelium (OSE), account for approximately 60% of all ovarian tumours and 90% of malignant ovarian cancers.…”
mentioning
confidence: 99%